Postshock Thermally Induced Transformations in Experimentally Shocked Magnetite. (24th March 2018) - Kontny, A.; Reznik, B.; Boubnov, A.; Göttlicher, J.; Steininger, R.
Abstract: We studied the effect of 973 K heating in argon atmosphere on the magnetic and structural properties of a magnetite‐bearing ore, which was previously exposed to laboratory shock waves between 5 and 30 GPa. For this purpose magnetic properties were studied using temperature‐dependent magnetic susceptibility, magnetic hysteresis and low‐temperature saturation isothermal remanent magnetization. Structural properties of magnetite were analyzed using X‐ray diffraction, high‐resolution scanning electron microscopy and synchrotron‐assisted X‐ray absorption spectroscopy. The shock‐induced changes include magnetic domain size reduction due to brittle and ductile deformation features and an increase in Verwey transition temperature due to lattice distortion. After heating, the crystal lattice is relaxed and apparent crystallite size is increased suggesting a recovery of lattice defects documented by a mosaic recrystallization texture. The structural changes correlate with modifications in magnetic domain state recorded by temperature‐dependent magnetic susceptibility, hysteresis properties and low‐temperature saturation isothermal remanent magnetization. These alterations in both, magnetic and structural properties of magnetite can be used to assess impact‐related magnetic anomalies in impact structures with a high temperature overprint. Key Points: The effect of 973 K heat treatment on magnetic and structural properties of experimentally shocked magnetite was studied Magnetic domain state is controlled by annealing of lattice defects during magnetite recrystallization These data contribute to the understanding of formation mechanisms of magnetic anomalies in large impact craters